GADGETS, INTERNET, SOCIAL MEDIA (Ustozlar uchun, 2025)
This article provides an in-depth exploration of how modern gadgets, the internet, and social media have transformed everyday life, communication, education, productivity, and global connectivity. It examines the rapid evolution of digital devices—from smartphones and tablets to wearable technologies—and analyzes their influence on human behavior and social interaction. The paper also highlights the internet's expanding role as the foundation of contemporary information exchange, enabling instant access to knowledge, e-commerce, online services, and remote collaboration. Furthermore, it evaluates the growing impact of social media platforms on personal identity, cultural trends, marketing strategies, and community building, while addressing the psychological and social challenges associated with excessive screen time, misinformation, digital addiction, privacy risks, and cyberbullying. By balancing benefits and drawbacks, the article discusses the necessity of digital addiction